The Influence of Brand Ambassador and Electronic Word Of Mouth (E-WOM) on Brand Switching in Tokopedia Applications (Jurnal Ilmiah Administrasi Bisnis dan Inovasi, 2023)
In the era of globalization, the world of information and communication technology continues to advance and develop. Technological developments help humans in completing work more easily. Technological developments also have an impact on all aspects of human life, one of which is the business world. . Tokopedia is one of the largest e-commerce platforms in Indonesia, where sellers and buyers meet on buying and selling sites. Tokopedia has succeeded in becoming one of the unicorn companies in Indonesia after eight years of existence. This study aims to determine the influence of Brand Ambassadors and Electronic Word of Mouth (e-WOM) on brand switching in the Tokopedia application. The type of research used is quantitative research with a descriptive analysis method approach. Data collection was carried out by distributing questionnaires in the form of a Google form. The population in this study are consumers who visit the Tokopedia shopping site in the fourth quarter of 2020. The number of samples needed is 100 respondents with the criteria of being 17 years old and are consumers of Tokopedia users who have previously used other e-commerce applications. The sampling technique used is non-probability sampling technique. Data analysis technique using multiple linear regression analysis. The results of this study indicate that simultaneously Brand Ambassador and Electronic Word of Mouth (e-WOM) have a significant effect on Brand Switching. And partially simultaneously Brand Ambassador and Electronic Word of Mouth (e-WOM) have a significant effect on Brand Switching.